Significance of saturation index of certain clay minerals in shallow coastal groundwater, in and around Kalpakkam, Tamilnadu, India - Chidambaram, S.; Karmegam, U.; Sasidhar, P.; Prasanna, Mohan Viswanathan; Manivannan, R.; Arunachalam, S.; Manikandan, S.; Anandhan, P. (Indian Academy of Sciences, 2011)
The saturation index of clay minerals like Gibbsite, Kaolinite, Illite, Montmorillonite and Chlorite in groundwater were studied in detail by collecting 29 groundwater samples from the shallow coastal aquifers in and around Kalpakkam. The samples collected were analysed for major cations, anions and trace elements by using standard procedures. The study reveals that pH has a significant role in the saturation index (SI) of minerals. It also shows that the relationship of electrical conductivity to the SI of these minerals is not significant than that of the ionic strength, log pCO2 values, and alumina silica ratio have significant relation to the SI of these clay minerals. The SI of these clay minerals was spatially distributed to identify the areas of higher SI. Silica has good correlation to SI of Kaolinite, Gibbsite and Montmorillonite and Al has good correlation to SI of all the minerals except to that of Chlorite.